FUNGSI PERS SEBAGAI PENYEBARAN INFORMASI DALAM PENEGAKAN HUKUM DI INDONESIA - Syahriar, Irman (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2019)
This study aims to find interactions between the press and law enforcement, as well as the information function needs of the press for law enforcement. This type of research used in this research is descriptive research. Analysis of the data used is qualitative. The results showed that the press had a large role in law enforcement and the development of Indonesian national law. Interaction between the functions of the press and the principles of law enforcement stated above can be mutually supportive, but also can inhibit each other. According to Bagir Manan, there are at least three aspects of press relations with law enforcement. First; the press as an object of law enforcement or affected by law enforcement. Second; the press as a facilitator of law enforcement.Third; the press as a barrier to law enforcement.